Synthesis and evaluation of the HIF-1α inhibitory activity of 3(5)-substituted-4-(quinolin-4-yl)- and 4-(2-phenylpyridin-4-yl)pyrazoles as inhibitors of ALK5. Issue 2 (15th January 2020) - Li, Yan-Wei; Li, Xiang-Yu; Li, Shanji; Zhao, Li-Min; Ma, Juan; Piao, Hu-Ri; Jiang, Zhe; Jin, Cheng Hua; Jin, Xuejun
Graphical abstract: Highlights: Six series of pyrazole derivatives were designed and synthesized. The effect of J-1012 on HIF-1α activation in HCT116 cells was investigated. J-1012 markedly decreased the hypoxia-induced or TNF-induced accumulation of HIF-1α protein dose-dependently. Abstract: The transcription factor hypoxia-inducible factor-1α (HIF-1α) plays an important role in apoptosis, metastasis, and proliferation and is recognized as an important potential therapeutic target for cancer. Six series of 3(5)-(6-methylpyridin-2-yl)-4-(quinolin-4-yl)pyrazoles (11a –d, 12a –d, and 18a –d ) and 3(5)-(6-methylpyridin-2-yl)-4-(2-phenyl-pyridin-4-yl)pyrazoles (19a –d, 20a –d, and 21a –d ) were synthesized and evaluated for activin receptor-like kinase 5 (ALK5) and HIF-1α inhibitory activity at the enzyme and cell levels. The effect of the lead compound 20d (J-1012 ) on HIF-1α activation in HCT116 cells was investigated. J-1012 markedly decreased the hypoxia-induced or TNF-induced accumulation of HIF-1α protein dose-dependently. Analysis revealed that J-1012 inhibited HIF-1α protein synthesis, without affecting the degradation of HIF-1α protein. Furthermore, by inhibiting the activation of HIF-1α, J-1012 suppressed the metastasis and proliferation and promoted apoptosis of HCT116 cells. These results suggest that J-1012 may be a potential therapeutic agent against human colon cancer.